2008
DOI: 10.1073/pnas.0708579105
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved gene family important for fat storage

Abstract: The ability to store fat in the form of cytoplasmic triglyceride droplets is conserved from Saccharomyces cerevisiae to humans. Although much is known regarding the composition and catabolism of lipid droplets, the molecular components necessary for the biogenesis of lipid droplets have remained obscure. Here we report the characterization of a conserved gene family important for lipid droplet formation named fat-inducing transcript (FIT). FIT1 and FIT2 are endoplasmic reticulum resident membrane proteins that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
289
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(323 citation statements)
references
References 36 publications
(38 reference statements)
21
289
0
1
Order By: Relevance
“…This result suggests that ADRP not only protects lipid esters from lipases, but it is also intimately related to the process of LD formation. It is intriguing that the ER membrane proteins FIT1 and FIT2 also appear to facilitate LD formation without enhancing TG synthesis or inhibiting lipolysis (Kadereit et al 2008). PAT proteins, as well as FIT1 and FIT2, are likely to constitute an active molecular mechanism making LDs from lipid ester in the membrane.…”
Section: General Lipid Droplet Functions Storage Of Lipid Estersmentioning
confidence: 99%
“…This result suggests that ADRP not only protects lipid esters from lipases, but it is also intimately related to the process of LD formation. It is intriguing that the ER membrane proteins FIT1 and FIT2 also appear to facilitate LD formation without enhancing TG synthesis or inhibiting lipolysis (Kadereit et al 2008). PAT proteins, as well as FIT1 and FIT2, are likely to constitute an active molecular mechanism making LDs from lipid ester in the membrane.…”
Section: General Lipid Droplet Functions Storage Of Lipid Estersmentioning
confidence: 99%
“…Mammals have a muscle-specific FIT protein (FIT1) that seems to be absent in worms; 22 it may be that the sole FIT protein in worms performs the functions of FIT1 and FIT2 in mammals. It has recently been found that the expression of the FIT1 gene is altered in patients with facioscapulohumeral muscular dystrophy (FSHD, discussed in 27 ).…”
mentioning
confidence: 99%
“…21 These proteins, called fat storageinducing transmembrane (FIT) proteins, are conserved and were first identified because, when over produced in mammalian cells, cause a dramatic increase in neutral lipid and LD production. 22 Humans have 2 of these proteins, FIT1, which is expressed in muscle, and FIT2, found in all tissues. 22 The yeast S. cerevisiae has 2 FIT2 homologs and lacks a homolog of FIT1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SCS3 gene was first identified as required for inositol prototrophy in the presence of choline, and it was reported that its inactivation triggered neither a reduction in the level of INO1 mRNA nor a decrease in the enzymatic activity of Ino1p (48). Recently, it was characterized as the yeast orthologue of a conserved gene family involved in lipid droplet formation (49). As for many other inositol auxotroph mutants analyzed here, the overexpression of NTE1 allowed scs3⌬ cells to grow in the absence of exogenous inositol (Fig.…”
Section: Inositol Auxotrophy Of Nte1⌬ Cells Is Due To a Defect In Tramentioning
confidence: 99%